COVID-19, corticosteroids and public health: a reappraisal. (August 2021) - Fernandes, M.; Brábek, J.
Abstract: Objectives: To assess whether regulatory guidance on the use of dexamethasone in hospitalised COVID-19 patients is applicable to the larger population of COVID-19 cases. The surge in worldwide demand for dexamethasone suggests that the guidance, although correct, has not emphasised the danger of its wider use. Study design: Data from the Randomised Evaluation of COVID-19 Therapy (RECOVERY) trial and the World Health Organisation (WHO) prospective meta-analysis have been deconstructed and analysed. Methods: To provide context, relevant publications were identified in PubMed using the following keywords: COVID-19, RECOVERY trial, WHO meta-analysis, variants, immunity, public health. Results: The WHO guidance 'Corticosteroids for COVID-19' was based on their prospective meta-analysis. This meta-analysis was weighted by data from the RECOVERY trial. Conclusions: In terms of COVID-19, dexamethasone has value in a narrow indication, namely, in hospitalised patients requiring respiratory support. The media blitz likely resulted in the wider use of dexamethasone in outpatients and as a preventive medication. This is reflected in the surge in worldwide demand for dexamethasone. We ask whether the use of steroids, beyond regulatory indications, may be responsible for the recent increase in mortality and especially the emergence of mucormycosis? From the public health standpoint, the current guidance for use of dexamethasone in COVID-19 could benefit from clarification and the addition of a cautionary note.